Wide Field-of-View Imaging With Wavefront Coded Diffractive Photon Sieves - Xiaonan Zhao; Jingpei Hu; Feng Xu; Aijiao Zhu; Chinhua Wang (IEEE Photonics Journal)
We report a demonstration of a wide field-of-view (FOV) imaging with a wavefront coded diffractive photon sieves. In conventional diffractive photon sieves (or other diffractive optical elements), clear imaging can only be achieved within near-zero FOV due to the strict interference conditions imposed by diffraction imaging. It is found that a wide FOV imaging with diffractive elements can be achieved by using a wavefront coded diffractive pattern that generates equal focusing power for light rays coming from a wide incident FOV. Experimental validation was performed using an ultraviolet (UV)-lithography fabricated wavefront coded photon sieves of a focal length of 500 mm and a diameter of 50 mm at a design wavelength of 632.8 nm. Results show that a wide half-FOV of 4° can be obtained with the wavefront coded photon sieves, compared to that of 0.5° with the conventional one.